Analisis Statistical Quality Control (SQC) dalam Upaya Mengurangi Jumlah Produk Cacat di PT X - Fadillah, Rayhan; Sari, Rianita Puspa (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
This study aims to analyze the application of the Statistical Quality Control (SQC) method in identifying and reducing the number of defective products in part A products at PT X. The data used includes the number of production and defects from June to December 2023. The SQC method is applied with the Seven Tools approach, namely check sheets, control charts, scatter diagrams, histograms, Pareto diagrams, fishbone diagrams, and flowcharts. The results of the analysis showed that the most dominant type of defect was weld holes, with a percentage of 95.5%. The main factors causing defects come from humans, machines, and production methods. The recommendations given include operator training, regular machine maintenance, the preparation of stricter work procedures, and increased production supervision. With the implementation of these improvements, the company is expected to reduce the defect rate and improve product efficiency and quality. Keywords : Produk Cacat, Statistical Quality Control, Seven Tools, SQC.